Combining transdermal and breath alcohol assessments, real‐time drink logs and retrospective self‐reports to measure alcohol consumption and intoxication across a multi‐day music festival. (10th November 2020) - Norman, Thomas; Peacock, Amy; Ferguson, Stuart G.; Kuntsche, Emmanuel; Bruno, Raimondo
Abstract: Introduction and Aims: Comprehensively investigating alcohol‐related behaviours in the context of a dynamic multi‐day alcohol‐licensed event is important for understanding and minimising patron risk. We aimed to assess the measurement utility of implementing a multi‐dimensional alcohol assessment battery using biometric data collection, real‐time drink logs and retrospective self‐report measures over the course of a 4‐day music festival. Methods: Fourteen adults participated ( n = 7 male, mean age 21.9 years). Breath and transdermal alcohol concentration (BrAC and TAC, respectively) were measured using breathalysers and transdermal alcohol bracelets. A real‐time drink log was completed via smartphones on initiating each drink, and a retrospective questionnaire was administered up to twice daily throughout the event (6 timepoints total). Results: While almost all participants (92.9%) logged significantly fewer drinks in real‐time than they retrospectively reported via the twice‐daily questionnaires, logs provided important contextual information including the types of drinks consumed and drinking intensity. Compared to BrAC, TAC provided a better understanding of the time course of intoxication, indicating highest alcohol consumption outside of static BrAC assessment windows. However, BrAC provided a better assessment of present state: all participants were 0.00% BrAC at departure despite over two‐fifths (42.9%) of the sample's last TAC reading exceeding 0.00%. Conclusions: As standalone assessments, each method possessed limitations. As a combined battery, they were successfully administered simultaneously, resulting in a more comprehensive overview of alcohol consumption/intoxication over the prolonged drinking session. However, the marked burden of simultaneous administration should be considered, and measures should be chosen judiciously based on research needs.